2010
DOI: 10.1111/j.1365-2621.2009.02138.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of cellular locus of limonin biotransforming enzyme in Pseudomonas putida

Abstract: Limonin is a highly oxygenated triterpene derivative of class of limonoids which causes delayed bitterness in citrus. Pseudomonas putida (P. putida) is able to reduce 47% and 63% of limonin from juice serum extract and standard limonin, respectively. Biochemical studies with P. putida indicate that probably two metabolic pathways viz. 17-dehydrolimonoid and deoxylimonoid pathway exists in the test organism. Experimental results indicate that the enzyme limonoate dehydrogenase which is found to be localized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The compounds 13-epi-24,25,26,27,30-pentanordammarane and 13-epi-24,25,26,27,30-pentanorlanostane may be considered compound 16's closest parent hydrides (cf. the dammarane (17) and lanostane (18) structures in Figure 2). may be considered compound 16's closest parent hydrides (cf.…”
Section: Chemistry and Classificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The compounds 13-epi-24,25,26,27,30-pentanordammarane and 13-epi-24,25,26,27,30-pentanorlanostane may be considered compound 16's closest parent hydrides (cf. the dammarane (17) and lanostane (18) structures in Figure 2). may be considered compound 16's closest parent hydrides (cf.…”
Section: Chemistry and Classificationsmentioning
confidence: 99%
“…may be considered compound 16's closest parent hydrides (cf. the dammarane (17) and lanostane (18) The term "protolimonoid" [37,41] to indicate reference molecular entities like 16 should be discouraged since properly called protolimonoids (also named protomeliacins or melianes [42]) are (a) naturally occurring compounds; (b) bear an intact (eventually oxygenated) dammarane-like C-17 side chain [43]; and (c) seem to be biogenetically related to limonoids as biochemical precursors [42][43][44], while the synthetic compound 16 [41] that bears a furan ring at position C-17 has not been detected in the plant kingdom.…”
Section: Chemistry and Classificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon optimization of the significant variables for permeabilization of P. putida G7, the surface plots helped in the better understanding of the interactions of the significant variables and thus enabled the determination of the optimal level of each variable for maximizing limonin bioconversion. The slightly lower rates of limonin bioconversion by permeabilized cells observed while treating citrus juice may be attributed to the components of the juice (like essential oils) leading to a possible loss of enzyme activity (Verma et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies reported the ability of a Pseudomonas putida G7 to biotransform limonin (Ghosh et al 2006) by virtue of a periplasmically located dehydrogenase which converts limonin to nonbitter derivatives (Verma et al 2010). Recently, we reported that permeabilization could improve the limonin bioconversion potential of P. putida (Malik et al 2011).…”
Section: Introductionmentioning
confidence: 96%